Retrospective review of bladder biopsy instead of skin biopsy provided clue for the diagnosis of neuronal intranuclear inclusion disease - Liu, Jun; Hu, Zhenzhu; Tan, Weihong; Li, Ying; Chen, Hao (Frontiers in Neuroscience, 2024)
The purpose of this study is to present a case of a patient with a negative skin biopsy who was diagnosed with neuronal intranuclear inclusion disease (NIID) through a retrospective review of a bladder biopsy specimen obtained 10 years ago. The patient initially presented with encephalitis-like symptoms, including fever, headache, and abnormal mental behavior. However, the DWI hyperintensity in the corticomedullary junction indicated the possibility of NIID. Due to the negative results of the skin biopsy, we initially refrained from hastily diagnosing the patient with NIID. However, 6 months later, the patient was readmitted to the hospital due to similar symptoms, and a follow-up MRI showed significant enlargement of the lesions at the corticomedullary junction. This time we identified intranuclear inclusions in her tissue specimens from bladder surgery. Subsequently, genetic testing was performed, leading to the diagnosis of NIID in the patient. Our case report indicates that detecting intranuclear inclusions from previous surgical specimens, rather than relying solely on skin biopsy, could significantly enhance diagnostic methods for NIID.